Praktek Bisnis Maslahat Dalam Perspektif Musannif - Syahputra, Angga; Khairina, Khalish (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2022)
Economic practices carried out by many parties in fact do not all bring benefits. Because many only consider profit and personal interest. KPPU itself stated that for a long time big businessmen had run unfair business by taking advantage of loopholes in power, guarantees and special access. However, the facts described above contradict what Anif did. Initial findings of researchers, Anif is not just money oriented. The impression of a businessman who acts for personal interests, does not care about the environment and society, is far from Anif's personality. For this reason, the researcher wants to examine more deeply about the concept of benefit in business practices carried out by Anif. This study uses a literature study by conducting a detailed study of H. Anif's profile book and is supported by previous studies as a secondary source. The results of the study show that Anif has succeeded in bringing benefits to the various businesses he runs. The concept of protecting religion, self, reason, family and property can be applied simultaneously by Anif.